"We Are Here to Assist All Individuals Who Need Hospice Services": Hospices' Perspectives on Improving Access and Inclusion for Racial/Ethnic Minorities. (May 2020) - Hughes, M. Courtney; Vernon, Erin
Background: Racial/ethnic minority populations in the United States are less likely to utilize hospice services nearing their end of life, potentially diminishing their quality of care while also increasing medical costs.Objective: Explore the minority hospice utilization gap from the hospice perspective by examining perceived barriers and facilitators as well as practices and policies.Method: Qualitative surveys were conducted with 41 hospices across the United States. Qualitative data analysis included performing a limited content analysis, including the identification of themes and representative quotations.Results: Commonly reported barriers to hospice care for racial/ethnic minorities included culture/beliefs, mistrust of the medical system, and language barriers. A major theme pertaining to successful minority hospice enrollment was an inclusive culture that provided language services, staff cultural training, and a diverse staff. Another major theme was the importance of community outreach activities that extended beyond the medical community and forming relationships with churches, racial/ethnic minority community leaders, and Native American reservations.Conclusion: The importance of incorporating a culture of inclusivity by forming committees, providing language services, and offering culturally competent care emerged in this qualitative study. Building strong external relationships with community groups such as churches is a strategy used to increase racial/ethnic minority utilization of hospice.